In-vitro cytotoxicity assessment of carbon-nanodot-conjugated Fe-aminoclay (CD-FeAC) and its bio-imaging applications. Issue 1 (December 2015) - Kang, Kyoung; Lee, Hyun; Kim, Moon; Park, So; Chang, Sung-Jin; Park, Ji-Ho; Huh, Yun; Lee, Jouhahn; Yang, Mino; Lee, Young-Chul; Park, Hyun
Abstract We have investigated the cytotoxic assay of Fe-aminoclay (FeAC) nanoparticles (NPs) and simultaneous imaging in HeLa cells by photoluminescent carbon nanodots (CD) conjugation. Non-cytotoxic, photostable, and CD NPs are conjugated with cationic FeAC NPs where CD NPs play a role in bio-imaging and FeAC NPs act as a substrate for CD conjugation and help to uptake of NPs into cancer cells due to positively charged surface of FeAC NPs in physiological media. As increase of CD-FeAC NPs loading in HeLa cell in vitro, it showed slight cytotoxicity at 1000 μg/mL but no cytotoxicity for normal cells up to concentration of 1000 μg/mL confirmed by two 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) and neutral red (NR) assays, with further observations by 4′, 6-diamidino-2-phenylindole (DAPI) stained confocal microscopy images, possessing that CD-FeAC NPs can be used as potential drug delivery platforms in cancer cells with simultaneous imaging.Graphical abstract CD conjugation with organo-building blocks of delaminated FeAC NPs